In situ axial vascularization for regeneration of challenging mandibular defects, a feasibility trial and case report with long-term results - Eweida, Ahmad; Morsi, Mohamed; Abouelnaga, Shady; Shokri, Naglaa; Schulte, Matthias; Kneser, Ulrich; Marei, Mona K. (Journal of cranio-maxillofacial surgery, 2025)
Reconstructing mandibular defects using tissue engineering and regenerative modalities as an alternative to free flap surgery is a challenging procedure especially after cancer resection, irradiation or multiple surgeries due to the suboptimal local vascularity. In such cases using a mandibular construct without a dedicated vascular supply carries the risk of central necrosis and failure. We present an in situ vascularization of a tissue engineered mandibular construct with long term results up to 60 months. A 46-year-old male presented with a large marginal mandibular defect following 4 previous resections of recurrent ameloblastoma complicated with mandibular fracture. Mandibular reconstruction was performed using a tissue engineered construct and in situ vascularized using an arteriovenous loop formed of a cephalic vein graft microsurgically anastomosed to the lingual artery and a tributary of the internal jugular vein. After 24 months, bone biopsies were obtained during insertion of the implants for dental rehabilitation and showed mature bone formation with upregulation of bone specific genes via PCR. Follow-up till 60 months confirmed a stable bone formation and functioning dental rehabilitation. The current study represents a step towards applying the modalities of regenerative medicine in complicated cases of craniofacial reconstruction otherwise requiring free flap surgery for bony reconstruction. - Clinical trial registration number - NCT04001842.
Online verfügbar: 12. März 2025, Artikelversion: 6. Juni 2025
Gesehen am 17.10.2025